2014
DOI: 10.1097/htr.0b013e318289ede5
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Integrity and Neuropsychological Performance After Traumatic Brain Injury

Abstract: Objective To conduct a detailed analysis of DTI parameters [fractional anisotropy (FA) and radial diffusivity (RD)] to evaluate white matter integrity in the corpus callosum (CC), and to examine correlations between DTI data and performance on multiple measures of cognitive functioning. Method 12 participants with a history of complicated mild, moderate, or severe TBI, and 12 control participants completed both standardized and experimental neuropsychological testing and an FMRI session, including DTI. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 43 publications
8
49
1
1
Order By: Relevance
“…This decrease is associated with cognitive impairments and disruptions in white matter integrity after injury (Arenth, Russell, Scanlon, Kessler, & Ricker, 2014;Niogi et al, 2008;Spitz, Maller, O'Sullivan, & Ponsford, 2013). The microglial clusters we observed in this study could be one of the underlying factors affecting FA after TBI.…”
Section: Microglial Clusterssupporting
confidence: 55%
“…This decrease is associated with cognitive impairments and disruptions in white matter integrity after injury (Arenth, Russell, Scanlon, Kessler, & Ricker, 2014;Niogi et al, 2008;Spitz, Maller, O'Sullivan, & Ponsford, 2013). The microglial clusters we observed in this study could be one of the underlying factors affecting FA after TBI.…”
Section: Microglial Clusterssupporting
confidence: 55%
“…Callosal damage disrupts this communication, affecting perception 24 and causing traditional symptoms of mTBI such as disorientation, amnesia, and impaired visual judgment 77 . Recently, diffusion tensor imaging found that disruption in the corpus callosum impaired performance after brain trauma, both in cognitive tasks and reaction time 4 . The axonal fibers in the corpus callosum responsible for this interhemispheric communication are highly organized directionally left-right.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes indicate the need for more adequate methods of feature extraction for this modality. The use of all FA voxels did not exclude any of the important brain areas mentioned by other studies, 7,11,12,45 supporting the possibility of high classification performance.…”
Section: Classification Performancementioning
confidence: 79%
“…10 Axonal injuries in white matter seem to concentrate in some important areas of white matter content including genu and splenium of the corpus callosum, the corona radiata, and the internal capsule. 5,7,11,12 The integrity of these and other affected areas is important for normal brain function, because white matter structure reflects functional connections between different areas of the brain. 13,14 Therefore, brain connectivity across the whole brain of patients with mTBI might be compromised because of disconnections occurring as a consequence of injured white matter tracks.…”
Section: Introductionmentioning
confidence: 99%